2021
DOI: 10.1177/14759217211008969
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage monitoring for metallic panels based on acoustic emission and adaptive improvement variational mode decomposition–wavelet packet transform

Abstract: The metallic panel acoustic emission signal with strong non-stationary properties is normally composed of multiple components (e.g. impulses, background noise, and other external signal), where impulses relevant to metallic panel are easily contaminated by background noise and other external signal, making it difficult to excavate the inherent acoustic emission signal features. To address this issue and achieve the damage monitoring of metallic panels based on acoustic emission technology, a new scheme based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…VMD is a completely non‐recursive decomposition algorithm, in which the modes are extracted simultaneously, and it has been widely applied in AE signal feature extraction 9 . As is well‐known, mode number K and balance parameter a play a key role in VMD, but it is difficult to empirically determine the two parameters.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…VMD is a completely non‐recursive decomposition algorithm, in which the modes are extracted simultaneously, and it has been widely applied in AE signal feature extraction 9 . As is well‐known, mode number K and balance parameter a play a key role in VMD, but it is difficult to empirically determine the two parameters.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…VMD is a completely non-recursive decomposition algorithm, in which the modes are extracted simultaneously, and it has been widely applied in AE signal feature extraction. 9 As is well-known, mode number K and balance parameter a play a key role in VMD, but it is difficult to empirically determine the two parameters. Previous studies have shown that the mode bandwidth decreases as a increases, and the mode with large bandwidth may contain excessive interference, while the mode with small bandwidth may weaken the fault information.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations